PENGARUH KONTEN EDUKASI DAN KONTEN REKREASI TERHADAP MINAT BERKUNJUNG SERTA DAMPAKNYA PADA KEPUTUSAN BERKUNJUNG - Nurbaiti, Dewi; Nurjanah, Siti (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
One of kind base human life needed is healthy, between the supporting healthy factors either sports are filling the happiness so that can create the healthy of body and soul. In order to fill life needs for the comfortness and freshness is going to some recreation place. One of innovation that is developing is the combination of education and recreation. This study aims are to analyze the regression of educational content and recreational content on the interest of visiting and the effect on the visiting decision. By the results of this study found that the educational content and recreational content are hava significants affect on the interest of visiting, and the educational content also directly affect on the visiting decision, without going through by the process of the visiting interest. People can directly decide to visit because there are provide some educational content that has same neededs of their needed. Keywords: education content, recreation content, visiting decision, visiting interest